Happiness in Plato and Aristotle (Research, Society and Development, 2021)
The present manuscript has the maximum purpose of analyzing the very sensitive and very important theme for philosophy: “Felicidade” in Plato. In this vein, this article, through exploratory research, of a qualitative nature, deductive method, collection of bibliographic document data, proceeded in order to carry out a thorough analysis of the doctrinal framework about the philosopher Plato, with the intention of making an approach to From the treatment presented by him, in the analysis of the situation contained in the initial story, the main question found was the one that involves the concept of happiness, formulated in the question. It is, therefore, a search for a clear, coherent and elucidative answer to this question and one that has a universal character, that is, one that applies to all cases or people, as these are important characteristics of a philosophical response. Finally, it is emphasized that the relevance of philosophical activity in seeking the definition of philosophy, bearing in mind that the relationship between philosophy and happiness is fundamental, since happiness would be the ultimate purpose of philosophy.